RENCANA STRATEGIS PENGEMBANGAN INFRASTRUKTUR JARINGAN INTERNET DI BIZNET MENGGUNAKAN METODE TOGAF - Syam, Riri Nurdina; Sudiatmika, I Putu Gede Abdi; Putra, Ida Ayu Gde Suwiprabayanti (Universitas Tabanan, 2023)
Internet Service Provider (ISP) is a company that provides internet services. Technological developments and changes in human behavior require ISPs to develop their services effectively and efficiently to face competition. The internet network infrastructure that is currently being used is felt to be not adaptive enough in responding to solutions to technological changes appropriately. In this study, using the research object at Biznet and assisted by the TOGAF research method. The Open Group Architecture Framework (TOGAF) is an enterprise architecture framework that provides a comprehensive approach to the design, planning, implementation and governance of corporate information architectures. This architecture is usually modeled by four levels or domains, namely business, applications, data and technology. In this study, it proven that TOGAF is the right method in making a better internet network infrastructure development strategic plan. The research process has several phases, namely Preliminary Phase, Architecture Vision, Business Architecture, Information Systems Architectures, Technology Architecture, Opportunities and Solutions, Migration Planning, Implementation Governance, and Change Management. This research testing method is the result of a Forum Group Discussion (FGD) which produces a business process design, information system and network topology that can be used as a reference for the development of internet network infrastructure at Biznet